Perspectiva de docentes bacharéis sobre a inclusão de pessoas com deficiência : o caso do Instituto Federal de Sergipe - Campus Lagarto - Pereira, Telma Amélia de Souza (2017)
The present study aims to investigate the perspectives of the bachelors teachers of the Federal Institute of Sergipe - Câmpus Lagarto on an inclusion of people with disabilities in professional and technological education. In order to achieve this goal, it was necessary to think of the teaching methods provided by the Institute and to evaluate within these methods which ones are in consonance with the law on an educational inclusion, in particular, an inclusion of the person with a disability. In this institutional gear, the main focus of the research is the teaching professionals who work in it. Considering that the graduates have pedagogical training to act as teachers, the main subject of this research are specifically the teachers who have bachelor degree, the way in which they think about the teaching and its relation with the inclusion of the disabled person in professional and technological education . The research approach is qualitative, of the case study type, with documental basis, with questionnaires and interviews, the time frame is based on Law 11,892 / 2008. For data analysis we used the content analysis method. The institutional actions have little visibility according to the informants and the training of teachers to work in professional education reflects on the pedagogical activity with students with disabilities and their perspective on the insertion of these in professional practices in the context of the Lagarto Câmpus, thus, continued education can be seen as a necessary element in teaching practice, as well as a (re) structuring of institutional policies with a view to the inclusion of persons with disabilities.